Observations on Provenance Variation in Pinus kesiya Royle Ex Gordon Using Rapd Markers - Ginwal, H. S.; Jadon, Vikas Singh (Indian Forester, 2009)
Twelve provenances of Pinus kesiya representing India (Assam, Meghalaya), Thailand, Vietnam, Philippines and Zambia from the natural range of distribution were evaluated for genetic diversity using the RAPD markers. Eighteen random decamer primers were used to assess variation. A total of 227 amplified products were generated, out of which 179 amplicons were polymorphic. All selected primers produced polymorphic amplification products, however, the extent of polymorphism varied with each primer. Amplification products obtained per primer ranged from as low as 8 to a maximum of 20, with an average of 12.61 per primer. Genetic divergence in respect of per cent polymorphism ranged from 50 to 92%, with an average of 79 %. The value of similarity coefficient varied between 0.44 and 0.72. The genetic similarity coefficient matrix indicated a fair range of variability between the provenances of P. kesiya. Highly divergent provenances were Zambia and Assam (India). Also one provenance of Philippines viz. Phil 7 showed high level of divergence with the Indian (Assam) provenance. These provenances revealed a considerable genetic distance with other provenances. The UPGMA dendrogram classified the provenances of P. kesiya into only two distinct clusters sharing 10 provenances in first cluster and one provenance in second one.